(untitled) (The Harvest, 2025)
This concept paper delves into the complexities of managing and regulating a residential high school, emphasizing the implementation of transformational leadership to bolster both academic excellence and holistic development. Recognizing the paramount importance of strong leadership, the paper underscores the necessity of cultivating a safe, inclusive, and equitable learning environment. The outlined comprehensive five-year strategic plan is multifaceted, addressing key areas such as curriculum enhancement, faculty development, technology integration, extracurricular programs, and stakeholder engagement. The plan further emphasizes financial stability and economic independence, achieved through strategic financial adjustments and active community engagement. A critical component of this strategy is fostering a supportive work environment, which is integral to the application of effective leadership principles. The paper argues that through the promotion of transformational leadership, residential high schools can achieve long-term sustainability, heightened academic excellence, and a robust educational culture. The study draws upon secondary sources, including scholarly articles, reports, and case studies, to provide a solid theoretical foundation. Additionally, it integrates insights and practical knowledge derived from my own professional experiences in educational leadership and administration. By combining these elements, the paper offers a comprehensive and practical roadmap for the successful management of residential high schools, ensuring they can thrive and adapt to an ever-evolving educational landscape.